A Web-Based Sexual Violence, Alcohol Misuse, and Bystander Intervention Program for College Women (RealConsent): Randomized Controlled Trial - Laura Francisca Salazar; Anne Marie Schipani-McLaughlin; Yesser Sebeh; Zainab Nizam; Matt Hayat (JMIR Publications, 2023)
BackgroundSexual violence (SV) incidence among college women has been invariant for the past 20 years. Innovative prevention strategies that are low resource and technology driven but demonstrate efficacy are greatly needed. ObjectiveThe aim of this study was to determine the efficacy of a novel theoretically driven internet-based intervention for first-year college students who identify as women (RealConsent) in reducing their risk of exposure to SV and alcohol misuse as well as increasing alcohol protective and bystander behaviors. MethodsThis randomized controlled trial involved first-year college students who identified as women (n=881) attending 1 of 3 universities in the southeastern United States. Participants aged 18 to 20 years were randomized to RealConsent (444/881, 50.4%) or to an attention-matched placebo control (437/881, 49.6%). RealConsent is fully automated and consists of four 45-minute modules that incorporate entertainment-education media and proven behavior change techniques. The primary outcome was exposure to SV; the secondary outcomes were alcohol protective behaviors, dating risk behaviors, alcohol misuse, and bystander behavior. Study outcomes were assessed at baseline and 6-month follow-up. ResultsAmong participants with some exposure to SV, those in the RealConsent group experienced less exposure to SV than the placebo group (adjusted incidence rate ratio 0.48, 95% CI 0.33-0.69; P=.002). Furthermore, participants in the RealConsent group engaged in more alcohol protective behaviors (adjusted odds ratio 1.17, 95% CI 0.12-2.22; P=.03) and were less likely to binge drink (adjusted incidence rate ratio 0.81, 95% CI 0.67-0.97; P=.003). Finally, participants in the RealConsent group who had 100% dosage were more likely to engage in bystander behavior than those with <100% dosage plus placebo group (adjusted odds ratio 1.72, 95% CI 1.17-2.55; P=.006). ConclusionsA comprehensive exposure to SV, alcohol use, and bystander educational program was successful in decreasing the occurrence of exposure to SV among those most at risk and in increasing alcohol protective behaviors. Because of its web-based and mobile technologies, RealConsent can be easily disseminated and holds potential for reducing campus SV. Trial RegistrationClinicalTrials.gov NCT03726437; https://clinicaltrials.gov/ct2/show/NCT03726437